A Translation Analysis of Passive Voice Sentence in Journey And Its Translation - HASTYANTI, YASINTA PUTRI (2012)
The objectives of the study are to classify the translation shift of sentence structure English Passive voice into Indonesian novel Journey, to describe the equivalence of passive sentence in the novel Journey and its translation. The result of the study is intended to be a little contribution to the linguistic translation. This research is descriptive qualitative research. To collect the data, the writer uses documentation method. The writer observes and reads the novel to find the passive voice sentence and take them as data. Then the writer classifies them into several categories, and analyzes them by using Catford's translation shift theory. Based on the data analysis, the writer finds eight translation shift. They are: simple passive voice sentence translated into simple passive voice sentence, simple passive voice sentence translated into simple active voice sentence, complex passive voice sentence is translated into complex active voice sentence, compound-complex passive voice sentences translated into complex passive voice sentence, compound-complex passive voice sentence translated into compound passive voice sentence, compound passive voice sentence translated into complex passive voice sentence, complex passive voice sentence translated into simple passive voice sentence, complex passive voice sentence translated into simple passive voice sentence, compound-complex passive voice sentence translated into simple passive voice sentence. Then, based on the analysis, the writer found 61.53% data passive voice sentences in Journey are equivalent and 38.46% are non equivalent. Therefore, the writer hopes that this research paper can be meaningfull for student, translator and other researcher.